U-Pb zircon ages and (isotope) geochemical signatures of the Kamanjab Inlier (NW Namibia): constraints on Palaeoproterozoic crustal evolution along the southern Congo craton. - Kleinhanns, I. C.; Fullgraf, T.; Wilsky, F.; Nolte, N.; Fliegel, D.; Klemd, Reiner; Hansen, B. T. (Continent Formation Through Time, 2015)
The formation of the Kamanjab Inlier (KI) in NW Namibia is poorly known and constrained to Palaeoproterozoic times. With the Epupa complex (EC) and Grootfontein Inlier (GI), the KI marks the southwestern Congo craton margin. Our new geochemical data for granitoids and orthogneisses indicate formation along an active continental margin. Single zircon ages frame granitoid emplacement to 1.86–1.83 Ga, roughly 75 myr older than ages from the northern EC and approximately 100 myr younger than from the GI. The southern EC is the only known Archaean Namibian basement with ɛNd1.85 Ga of −10.2 to −6.3, in contrast to northern EC (−1.8 to 4.4) and KI (−6.2 to 2.6). Thus, earlier speculation that the southern EC is an exotic terrane, among the Namibian basement complexes, is supported by our data. In contrast, the KI is geochemically comparable to the northern EC and GI. The c. 2.0 Ga Lufubu metamorphic complex roughly 1000 km further east shows similar geochemistry, and a common evolution in the Kamanjab–Bangeweulu magmatic arc has already been proposed. Therefore, our new data point to a major Palaeoproterozoic crustal growth event at the southwestern margin of the Congo Craton starting in the present east and gradually moving towards the present NW.